MAC curve on three alternatives for livestock in Cauca and Valle del Cauca - Ruden, Alejandro (2019)
At present, there are innumerable alternatives to reduce greenhouse gas emissions from livestock production systems. However, the real potential of each alternative is unknown since it is subject to conditions specific to the regions where it is implemented as biophysical conditions and productive costs. The MAC curves evaluate the costs and mitigation potential of three technologies: improved pastures, improved pastures plus legumes and silvopastoral systems in the departments of Cauca and Valle del Cauca, Colombia. Silvopastoral systems proved to have the greatest mitigation potential and the lowest cost per tons of carbon mitigated